2018
DOI: 10.1016/j.jiac.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical factor associated with congenital cytomegalovirus infection in pregnant women with non-primary infection

Abstract: The aim of this nested case-control study was to evaluate clinical factors associated with the occurrence of congenital cytomegalovirus (CMV) infection in pregnant women with non-primary CMV infection. In a cohort study of CMV screening for 2193 pregnant women and their newborns, seven newborns with congenital CMV infection were identified among 1287 pregnant women with non-primary CMV infection that was defined as negative IgM and positive IgG with IgG avidity index >45%. In the 1287 women with non-primary CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…There is still uncertainty about whether symptoms can be addressed as reliable indicators of vertical transmission or disease severity [59][60][61]. Other infections that lead to congenital malformation, such as cytomegalovirus, also have a high number of asymptomatic cases, but, when present, symptoms might indicate an adverse outcome [62].…”
Section: Discussionmentioning
confidence: 99%
“…There is still uncertainty about whether symptoms can be addressed as reliable indicators of vertical transmission or disease severity [59][60][61]. Other infections that lead to congenital malformation, such as cytomegalovirus, also have a high number of asymptomatic cases, but, when present, symptoms might indicate an adverse outcome [62].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the frequency of changes in the decidua was higher in placentas from mothers with non-primary CMV infections than from those with primary infections. Recently, we reported that threatened premature delivery was associated with the occurrence of congenital CMV infections in pregnant women with non-primary CMV infections, the pathophysiology of which may be closely associated with CMV reactivation during pregnancy [21]. Threatened premature delivery may reflect the inflammatory conditions in which CMV is reactivated; alternatively, it may cause CMV reactivation in pregnant women.…”
Section: Fgrmentioning
confidence: 99%
“…There is still uncertainty if the symptoms can be addressed as reliable indicators of vertical transmission or disease severity [59][60][61]. Other infections that lead to congenital malformation, such as cytomegalovirus, also have a high number of asymptomatic cases, but, when present, symptoms might indicate an adverse outcome [62].…”
Section: Discussionmentioning
confidence: 99%